A comprehensive review of organic-inorganic composites based piezoelectric nanogenerators through material structure design. (20th October 2022) - Lu, Haowei; Zheng, Haiwu
Abstract: With the development and popularization of Internet of things, how to provide energy for distributed sensors, portable and embedded electronic devices have become a challenge. People's requirements for power supply equipment are portable, sustainable and free maintenance. Therefore, organic–inorganic composites based on piezoelectric nanogenerator (PENG) is becoming one of promising solutions due to these advantages of low cost, excellent mechanical property and environmental adaptability, which can effectively harvest ubiquitous micro-nano mechanical high entropy energy and convert it into electricity to power electronics and nano-systems. In this study, the development of PENGs based on organic–inorganic composites have been reviewed and several strategies toward high output performance of PENGs, including various materials, piezoelectric fillers modification and structural design are summarized and discussed. The effects of different optimization methods on short circuit current ( I SC ), open circuit voltage ( V OC ) and output power of various PENGs as well as current difficulty for improving performance have been discussed. Meanwhile, some specific application scenarios in previous reports are also presented. Finally, we have proposed an outlook about future developments of flexible PENG and authors hope that this review can help researchers better understand this field and facilitate the improvement of flexible PENG to realize a broader application in self-powered system.